122 Adaptive leadership & managing change in breast cancer services during the Covid-19 pandemic. (16th November 2020) - Mondani, Giuseppina; Sulieman, Mona; Potiszil, Kali; Abbas, Imran; King, Polly; English, Rachel; Brown, Iain; Drew, Philip
Abstract : COVID-19 pandemic evolved rapidly and necessitated rapid, dynamic service reorganisation. Utilisation and distribution of our individual team members' skillsets demonstrates our adaptive leadership across all aspects of the service. We adhered to the Association of Breast Surgeons guidelines for breast cancer care to downsize activity and resources. Objective of strategy was to maintain a consistent high standard of care, without compromising on NHS targets or cancer outcomes. Face-to-face appointments (FA) were minimised to reduce the risk of COVID-19 infection. A novel Vetting System stratified patients' symptom into High Risk of cancer (FA) or Low Risk (Telephone Consultation, TC). Detailed patient spreadsheets were created, accessible on a shared drive as a real time dashboard - monitoring patient flow, recording triage decisions & outcomes. We redesigned patient spaces with an 'in car' waiting room, single direction flow and patient-only admittance for clinic safety. We suspended non-essential services: to preserve hospital resources; reducing non-essential attendances and allowing re-deployment of staff to acute areas. Data comparison over same period the previous year was used to gain an idea of the impact of activity changes and to anticipate additional workload post-lockdown. March 23 to May 1st, 2020: 45 cancer surgery 296 new breast clinics 531 follow-ups (104 elected to postpone) 427 (331 TC, 96 FA) 26 breast screening March 25 to May 3rd, 2019: 53 cancer surgery 507 new breast clinics 674 follow-ups 32 breast screening Shortfall in new patients was related to reduced GP activity/patient reluctance to seek medical help. Shortfall in follow ups due to postponements. Subsequently clinical evaluation with patient experience questionnaires confirmed no cancer missed, no delays to treatment and no harm caused. Adaptive leadership was essential in a time of unprecedented challenges.